Predictors for the risk and severity of post-thrombotic syndrome in vascular Behcet's disease - ILGIN, CAN; ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER (ELSEVIER, 2021)
Objective: Deep vein thrombosis (DVT) of the lower extremities is the most common form of vascular involvement in Behcet disease (BD), frequently leading to post-thrombotic syndrome (PTS) as a disabling complication. We have described the clinical characteristics and predictors of PTS presence among patients with BD and lower extremity DVT. We also used venous Doppler ultrasound (US) examinations in our assessment. Methods: Patients with BD (n = 205; 166 men, 39 women; age 39 6 9.5 years) and a history of DVT were investigated. The Villalta scale was used to assess the presence and severity of PTS. Doppler US examinations were performed within 1 week of the clinical evaluation. The total number of vessels with reflux, thrombi, recanalization, and collateral vessels were calculated. Results: Of the 205 patients with BD, 62% had had PTS and 18% had had severe PTS. Patients with PTS had had greater reflux (P = .054) and thrombosis (P = .02) scores compared with patients without PTS. Treatment with anticoagulation (AC), immunosuppressive (IS) therapy, or AC combined with IS drugs did not affect the occurrence of PTS. However, patients treated with IS therapy, with or without AC drugs, had a decreased incidence of severe PTS compared with the AC-only group (P = .017). Patients treated with AC plus IS agents also had increased collateral scores compared with patients treated with only IS drugs. Interferon-a use seemed to provide better recanalization scores compared with azathioprine only (1.0 [range, 0-14] vs 2.5 [range, 0-10]; P = .010). Conclusions: Patients with BD and DVT have a high risk of developing severe PTS. IS treatment decreases the development of severe PTS. AC therapy might influence the course of PTS by increasing the collateral scores, and the use of interferon-a also increased recanalization scores. Routine assessment with Doppler US examinations could be helpful in the prediction of severe PTS. (J Vasc Surg Venous Lymphat Disord 2021;9:1451-9.)
Keywords: Anticoagulation; Behcet disease; Deep vein thrombosis; DVT; Immunosuppressive agents; Post-thrombotic syndrome; DEEP-VEIN THROMBOSIS; VENOUS DISEASE; 1ST EPISODE; FOLLOW-UP; QUALITY; THROMBOEMBOLISM; WARFARIN; SYSTEM; REFLUX